Access to Dental Care for Children and Young People in Care and Care Leavers: A Global Scoping Review - Jo Erwin; Jane Horrell; Hannah Wheat; Nick Axford; Lorna Burns; Joelle Booth; Robert Witton; Jill Shawe; Janine Doughty; Sarah Kaddour; Skye Boswell; Urshla Devalia; et al. (MDPI AG, 2024)
Aims: This scoping review aimed to explore three research questions: 1. What is the dental care access for children and young people (CYP) in care and care leavers? 2. What factors influence CYP in care and care leavers' access to dental care? 3. What pathways have been developed to improve access to oral health care for CYP in care and care leavers? Methods: Five databases (Ovid MEDLINE, Ovid Embase, CINAHL, SocINDEX and Dentistry and Oral Sciences Source) and grey literature sources were systematically searched. Articles relating to CYP in care or care leavers aged 0-25 years old, published up to January 2023 were included. Abstracts, posters and publications not in the English language were excluded. The data relating to dental care access were analysed using thematic analysis. Results: The search identified 942 articles, of which 247 were excluded as duplicates. A review of the titles and abstracts yielded 149 studies. Thirty-eight were eligible for inclusion in the review: thirty-three peer-reviewed articles, one PhD thesis and four grey literature sources. All papers were published from very high or medium Human Development Index countries. The studies indicate that despite having higher treatment needs, CYP in care and care leavers experience greater difficulty in accessing dental services than those not care-experienced. Organisational, psycho-social and logistical factors influence their access to dental care. Their experience of dental care may be impacted by adverse childhood events. Pathways to dental care have been developed, but little is known of their impact on access. There are very few studies that include care leavers. The voices of care-experienced CYP are missing from dental access research. Conclusions: care-experienced CYP are disadvantaged in their access to dental care, and there are significant barriers to their treatment needs being met.